2017
DOI: 10.1111/ejn.13690
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous processing in the striatal direct and indirect pathways: single body part sensitive type IIb neurons may express either dopamine receptor D1 or D2

Abstract: Striatal medium spiny projection neurons (MSNs) output through two diverging circuits, the 'direct and indirect pathways' which originate from minimally overlapping populations of MSNs expressing either the dopamine receptor D1 or the dopamine receptor D2. One modern theory of direct and indirect pathway function proposes that activation of direct pathway MSNs facilitates output of desired motor programs, while activation of indirect pathway MSNs inhibits competing motor programs. A separate theory suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…5; Kolomiets et al, 2003;Freeze et al, 2013;Brown et al, 2014). In our preparation, somesthetic stimulations potentially activating both pathways (Coffey et al, 2017) also produced inhibitory/excitatory patterns in the SNr (Fig. 1), similar to those previously described, but evoked by electrical stimulation of motor and premotor cortices (Antonazzo et al, 2019) or electrical and chemical activation of the striatum (Dray et al, 1976;Chevalier et al, 1985;Deniau and Chevalier, 1985).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…5; Kolomiets et al, 2003;Freeze et al, 2013;Brown et al, 2014). In our preparation, somesthetic stimulations potentially activating both pathways (Coffey et al, 2017) also produced inhibitory/excitatory patterns in the SNr (Fig. 1), similar to those previously described, but evoked by electrical stimulation of motor and premotor cortices (Antonazzo et al, 2019) or electrical and chemical activation of the striatum (Dray et al, 1976;Chevalier et al, 1985;Deniau and Chevalier, 1985).…”
Section: Discussionsupporting
confidence: 85%
“…1G, bottom). Thus, in this preparation, somesthetic stimulations produced somatosensory representations in the population dynamics of the SNr characterized by transient inhibitions followed by transient excitations, potentially reflecting a balanced direct-indirect pathway activation (Coffey et al, 2017).…”
Section: Somesthetic Stimulations In Anesthetized Animals Reflect Direct-indirect Pathway Activationmentioning
confidence: 80%
“…A role of the dorsal striatum in providing moment-to-moment movements representation can not be overlooked, as the dorsocentral/lateral striatal regions in which we (and others) recorded neuronal activity receive massive cortical input from motor and sensory regions related to movements and stimulation of different body parts, mainly the trunk, limbs and, to a lesser extent, oro-facial regions [13,14]. Moreover, it has been shown that the spiking activity of dorsal striatal putative FSI and direct and indirect-pathway PN is strongly modulated by passive manipulations of body parts in mice and rats [23,41]. Finally, large-scale calcium imaging of both direct and indirect-pathway PN activity has revealed that distinct behavioral patterns associated with openfield exploration are fully mapped in the dorsal striatum [42].…”
Section: Discussionmentioning
confidence: 92%
“…This possibility has not been directly tested but several recent works suggest that this interpretation should not be discarded. Coffey et al [47 ] used optrodes to identify dSPN and iSPN and found that about half of the recorded neurons in both populations increased their firing rate sharply in response to the passive stimulation of a given body part. In addition, it was shown in mice trained to perform a head-movements task that the firing rate of putative SPN is perfectly correlated with head-movements velocity [48].…”
Section: Somatosensory Responses and Action-related Neuronal Represenmentioning
confidence: 99%